Determining the graduates employability using data analytics model - Matos Jr., Zenon A. (Penerbit Universiti Kebangsaan Malaysia, 2023)
The graduate’s employability is one of the issues in the education sector. By molding its graduates with skills and knowledge in accordance to the industry, With the number of Bachelor of Science in Information Technology graduates increasing each year, we need to visualize and predict future employment. This will ultimately inform institutions and enable them to enhance their education delivery plans. These studies used a data analytics model to forecast the employability of graduates using the linear regression algorithm and the SMOreg algorithm, predict the number of graduates in the next 3 years in the BS Information Technology program, and determine the percentage of graduates who are employed and unemployed using the data sourced from the tracer study conducted. All data preparation and modeling are done using the Weka tool. The result shows that the majority of graduates are employed, whereas only 10% are unemployed. The majority of graduates employed are female, and 40% are male. Additionally, it is evident that there is an increasing pattern of the graduate’s employability and that there will be approximately a 14% increase in the employment rate for the next 3 years.